Pengaruh Komitmen Organisasi, Motivasi dan Kompensasi pada Kinerja Manajerial dengan Internal Locus Of Control sebagai Variabel Moderasi - Arief Adi Saputro; Joko Utomo (Business Management Analysis Journal (BMAJ), 2018)
This study is aimed to examine the effect of organization commitment, motivation and compensation to the managerial performance trough internal locus of control as a moderating variables. The object of this research is FKTP BPJS Health in Kudus Regency. As for the population in this study as many as 116 FKTP BPJS Health in Kudus Regency using population sample method. The analysis technique used is Structural Equation Modeling (SEM). The results of this study indicate that organization commitment, motivation and compensation had a significant effect on managerial performance, internal locus of control was also proven to be successful in strengthening the relationship between organizational commitment, motivation, and compensation with managerial performance of FKTP BPJS Health in Kudus Regency.